Optimal Portfolio Choice and the Valuation of Illiquid Securities - Longstaff, Francis A. (Review of Financial Studies, 2001)
Journal Article Optimal Portfolio Choice and the Valuation of Illiquid Securities Get access Francis A. Longstaff Francis A. Longstaff University of California, Los Angeles Address correspondence to Francis A. Longstaff, Anderson School, UCLA, Box 951481, Los Angeles, CA 90095-1481, or e-mail francis.longstaff@anderson.ucla.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 14, Issue 2, April 2001, Pages 407–431, https://doi.org/10.1093/rfs/14.2.407 Published: 21 June 2015